Personnel management - Bottomley, Michael H. (London : Pitman Publishing, 1983)
The text presents a summary of current knowledge. It is aimed at student who wishes to make personnel management a career, and also to students were forced to study personnel as part of a wider professional qualification.
Includes indexes.
Includes bibliographical references: p. [178]-185.
ne 12/07/2018
Loans
Keywords: Personnel management